Pengaruh Kepemimpinan Dan Budaya Organisasi Terhadap Komitmen Organisasi : Study Pada Pegawai BKD Dan PSDM Di Kabupaten Dompu - Nira Nurillah; Lalu Suparman; Mukmin Suryatni (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to determine the influence of leadership, organizational culture on organizational commitment at the BKD and PSDM offices in Dompu. The type of research used is causal associative research with a quantitative approach. The population and respondents in the research were 56 employees. The data collection method used was the census method. The data collection tool is a questionnaire. The analytical tool used is Multiple Linear Regression analysis using the SPSS version 25 program. The results of data analysis show that (1) Leadership has a positive and significant effect on Organizational Commitment at the BKD and PSDM offices in Dompu. (2) Organizational culture has a positive and significant effect on organizational commitment at the BKD and PSDM offices in Dompu.